Structured pain management reduces patient discomfort after catheter ablation and rhythm device surgery. (18th July 2017) - Dörschner, M.; Bollmann, A.; Dinov, B.; Richter, S.; Döring, M.; Arya, A.; Müssigbrodt, A.; Kircher, S.; Dagres, N.; Sommer, P.; Hindricks, G.; Bode, K.
Abstract: Background: The goal was to test the effectiveness of a structured pain management programme after invasive electrophysiological interventions in cardiology including ablation of atrial fibrillation (AF) or ventricular tachycardia (VT) and implantation, or explantation, of pacemakers or implantable cardioverter defibrillators. Methods: This was a prospective study with a pre‐/post‐design where a post‐intervention group (116 consecutive patients) was compared to a pre‐intervention group (102 consecutive patients) after implementation of a structured pain‐management programme using the numeric rating scale (NRS 0–10) and classified as moderate‐to‐severe if NRS > 3. Measurements were recorded every two hours during the first 24 h post‐operatively. The location of the pain and the amount of analgesic used were also recorded. Results: The proportion of patients who experienced moderate‐to‐severe pain after the procedure decreased after initiation of the pain‐management program: 47% versus 61%; p  =   0.048. This difference was driven primarily by reduced pain late (8–24 h) after the procedure; 16% versus 39%; p  <   0.001. The risk to develop late (8–24 h) post‐procedural pain was reduced approximately three‐fold after implementation of the pain‐management programme (OR = 0.32, 95% CI 0.16–0.64, p  =   0.001). Multivariate analysis indicated chronic pain, early pain (0–6 h), and type of intervention were associated with late post‐interventional pain. In contrast, age, diabetes mellitus, BMI, gender and procedure time were not related. Conclusion: The findings illustrate the potential value of a structured pain‐management programme. The proportion of patients who experienced moderate‐to‐severe pain after these electrophysiological procedures decreased significantly. Significance: This is the first exploratory study that evaluates the impact of a multidisciplinary pain‐management programme after cardiac electrophysiological interventions. It demonstrates that significant quality improvement is achievable following simple rules together with patient and staff education. The programme reduces the proportion of patients with moderate‐to‐severe pain after electrophysiological procedures significantly.